2015
DOI: 10.1080/08952833.2015.1030353
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling Sexual Identity in the Face of Marianismo

Abstract: Marianismo illustrates a gender role phenomenon common in Latina women, which implicitly socializes embodiment of virtues of the Virgin Mary, including caretaking, self-sacrifice, honor, passivity, and sexual morality. The authors suggest that problems may arise regarding sexual satisfaction, as sexual pleasure may conflict with the expectation of sexual morality. Integration of transgenerational and narrative therapies to facilitate sexual exploration throughout the acculturation process are proposed. Suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…An inverse relationship between gender roles and marianismo was observed where women with egalitarian attitudes showed lower marianismo beliefs. Marianismo is a traditional gender role that reflects being virtuous and chaste, a family and a spiritual pillar; subordinate to others, and self‐silencing to maintain harmony (Hussain et al, ; Wood & Price, ). A recent study by Piña‐Watson et al () examined marianismo along with gender roles among young adults in academic settings and demonstrated that young Latina women with strong “negative” marianismo beliefs were associated with poorer academic attitudes; however, “positive” marianismo was associated with nontraditional gender roles and more positive academic attitudes (Piña‐Watson et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An inverse relationship between gender roles and marianismo was observed where women with egalitarian attitudes showed lower marianismo beliefs. Marianismo is a traditional gender role that reflects being virtuous and chaste, a family and a spiritual pillar; subordinate to others, and self‐silencing to maintain harmony (Hussain et al, ; Wood & Price, ). A recent study by Piña‐Watson et al () examined marianismo along with gender roles among young adults in academic settings and demonstrated that young Latina women with strong “negative” marianismo beliefs were associated with poorer academic attitudes; however, “positive” marianismo was associated with nontraditional gender roles and more positive academic attitudes (Piña‐Watson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Latinas are expected to put their family's needs before their own personal interests, and to have strong aspirations for marriage and childbearing (Castillo et al, 2010;Ruiz et al, 2017). These cultural expectations highly influence gender role ideologies, sexual identity, and power balance in relationships among Latinas throughout their lifetimes (Hussain, Leija, Lewis, & Sanchez, 2015;Miville et al, 2017;Villarruel, 1998). As a result, women may submit to male dominance, frequently resulting in violence, lack of opportunity for personal development, and economic dependence on men (Castillo et al, 2010;Cianelli, Ferrer, & McElmurry, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, higher levels of acculturative stress at Time 2 subsequently predicted less of the Virtuous and Chaste and Subordinate to Others beliefs at Time 3. Such results suggest that endorsement of the belief that Latinas should be morally pure in thought and sexuality and should silence themselves to maintain positive relationships were associated with increased acculturative stress, possibly because of the burden of these marianista expectations (Nuñez et al, 2016) in the context of a new society with differing or conflicting norms related to sexual empowerment and egalitarian relationships (Hussain et al, 2015;Nuñez et al, 2016;Viana et al, 2017). In addition, Latina young adult immigrants may have been resolving their experience of acculturative stress, in part, by lessening their endorsement of the beliefs that Latinas should be virtuous and should be subordinate to others.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Virtuous and Chaste marianismo belief contrasts U.S. society beliefs of relatively more acceptance of premarital sexual behavior and greater sexual autonomy and pleasure for women. Latina immigrants who endorse the Virtuous and Chaste belief may experience higher levels of acculturative stress due to pressure to shift their beliefs and actions to align with the more sexually autonomous dominant cultural society (Hussain, Leija, Lewis, & Sanchez, 2015). Similarly, Latinas who believe they should be submissive to men (i.e., Subordinate to Others belief) and refrain from expressing their needs in relationships (i.e., Silencing Self to Maintain Harmony belief) to a greater extent may experience acculturative stress attributable to pressure to express their needs, explore relational conflict, and maintain more egalitarian relationships after immigration.…”
Section: Marianismo Beliefs and Acculturative Stressmentioning
confidence: 99%
“…There is a bias that identifying as gay or bisexual implies less masculinity, which contradicts expected Latinx gender roles for men (Marín, 2003). Similarly, marianismo implies a virtuous representation of females with expectations of self-sacrifice, caretaking, passiveness, and the upholding of traditional sexual moral values (Hussain et al, 2015). In addition, familismo emphasizes the importance of family harmony (Unger & Schwartz, 2012) and placing family needs ahead of the needs of individual family members (Calzada et al, 2010), a stance that may force LSMY to hide their sexual minority status due to conflict with ingrained cultural values (Craig & Keane, 2014).…”
mentioning
confidence: 99%